Value co-creation through virtual community participation - Ylikylä, Sauli (My University, 2012)
Consumers create a great deal of content in the Internet. As they do not get a monetary compensation for doing so, it seems apparent that other types of reward are derived from giving up one's time and other resources. The purpose of this study is to describe value creation and user participation in a virtual community. It can be broken down into three research questions. 1. What is the value creation logic of a virtual community? 2. What value is perceived by virtual community users? 3. What is the association between value perceived by virtual community users and their participation in a community? The study employs the discussion on value co-creation as well as perspectives on the notion of value for consumers to create a theoretical framework for value creation. To understand value creation in the context of virtual communities and to create a theoretical framework for user participation, existing literature and research on virtual communities is discussed. The empirical part of the study employs quantitative methodology to analyze data collected by sending a survey questionnaire to the users of a Finnish wellbeing-based virtual community. The results indicate that virtual community users perceive self-development, enjoyment, reputation-building and community commitment value when using the service and that value perceptions are associated with community participation. Moreover, it was found that different types of value are associated with different forms of participation. Based on the findings, it is suggested that the four types of value make up a considerable share of value for virtual community users. Moreover, as the results indicate that different value types are associated with different forms of participation, it suggested that virtual community organizers consider what forms of participation they want to promote and design their virtual communities to support creation of the different types of value accordingly.